Consumer acceptance and willingness to pay for edible insects as food in Kenya: the case of white winged termites - Mohammed H. Alemu; Søren Bøye Olsen; Suzanne E. Vedel; Kennedy O. Pambo; Victor O. Owino (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2015)
Edible insects are receiving substantial attention because of their potential as a significant future food source of high nutritional value and with important environmental benefits. As a result, there is a focus on the supply side to establish and optimize the insect production sector and develop the value chain. However, as the ultimate success of a product development depends on consumers' product judgement and acceptance, acquiring information about potential demand is of paramount importance for policy advice. In this paper, we aim to give a first insight into the potential demand for termite-based food products (TBFPs) in Kenya. We assess the demand in terms of consumer preferences and willingness to pay using a stated choice experiment method. A novel feature of this paper is that it focuses on how the termites should be presented and introduced, either as whole or processed, in a typical daily meal in order to increase consumer acceptance. Results from the latent class model reveal that consumers prefer and are willing to pay more for TBFPs with high nutritional value and when they are recommended by officials. In addition, results show that high to a very high food safety control levels of the TBFPs are valued positively by most consumers.
Keywords: D12; Q11; Q13; Q18; Q54; Q56; 330; Stated Choice Experiment; Edible insects; Latent class model; Termite-based food products; WTP